TINJAUAN YURIDIS PELAKSANAAN PERJANJIAN PEMBERIAN PINJAMAN BANTUAN MODAL BAGI USAHA KECIL DALAM PROGRAM KEMITRAAN PADA PT. AP II - MUHARROIMI SOUVANNY (PREMISE LAW JURNAL, 2016)
The agreement between PT Angkasa Pura II (Persero) and business partner embodied in the contract which is in accordance with Article 11 of the Regulation of the minister of State for BUMN No PER-09/MBU/07/2015 which is called Credit Contract because its nature is nearly the same as the credit in which fostered partners pay it by installment. The agreement is made in standard format in Article 3 on Evidence of Contract, Article 5 on Right and Obligation, Article 6 on Sanction, and Article 7 on Settling Overdue Payment. Besides that, in the contract is the charge for administrative service of 6% (six percent) per year of the credit limit which is contrary to the purpose of providing aid for business partners. When fostered partners are not able to return their loan, the effort to recover it is by rescheduling or by reconditioning. Keywords: Giving Credit, Small Businesses in Partnership Program